Caribbean Dolphin - (:unkn) unknown ([S.l., Norman Parkinson], 2011)
Description printed on the back of the postcard: "This is the Caribbean dolphin not to be confused with the porpoise. A most beautiful fish it comes from the sea like lapis lazuli." Postcard number 405.
Colour: Coloured; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Fishing--Trinidad and Tobago; Fishers--Trinidad and Tobago